Influence of Gradient Residual Stress and Tip Shape on Stress Fields Inside Indented TiN Hard Coating. Issue 11 (11th July 2021) - Todt, Juraj; Zalesak, Jakub; Krywka, Christina; Keckes, Jozef
Abstract : Nanoindentation of treated surfaces, thin films, and coatings is often used as a simple method to measure their hardness and stiffness. These quantities are technologically highly relevant and allow to qualitatively compare different material and surface treatments but fail to capture the entire extent of the highly complex mechanical interaction between indenter tip and the tested surface. Many studies have addressed this question by analytical or numerical modeling, but they must rely on verification by recalculating indentation curves or ex situ microscopy of surface deformation postexperiment. Herein, results from in situ measurements of the multiaxial stress distributions forming beneath an indenter tip while the tested sample is still under load are presented. A 9 μm‐thick TiN hard coating is tested in 1) as‐deposited state and 2) shot‐peened by Al2 O3 particles, using two diamond wedges as indenter tips, with 60° and 143° opening angle, respectively. The results reveal a strong influence of the tip shape on the deformation behavior and the main stress component developing inside the sample while under load. In addition, a crack‐closing effect can be attributed to the exponentially declining near‐surface compressive residual stress gradient that is present in the shot‐peened sample. Abstract : Stress distributions forming in a 9 μm‐thick nanocrystalline TiN film during indentation with wedged diamond tips of differing shapes are measured in situ using cross‐sectional X‐ray nanodiffraction. In addition, the influence of shot‐peening is studied. While tip shape has a major influence on the developing stress fields and the accompanying deformation mechanisms, shot‐peening helps prevent crack growth.